2007
DOI: 10.1088/0953-8984/19/25/256212
|View full text |Cite
|
Sign up to set email alerts
|

Thermal transport in (Y,Gd)Ba2(Cu1−xMnx)3O7−δforx≤0.02

Abstract: Thermal conductivity κ(T) and thermoelectric power S(T) studies on (Y,Gd)Ba2(Cu1−xMnx)3O7−δ (x≤0.02) superconductors are presented here. Thermal conductivity for all the samples exhibits a hump below the superconducting transition temperature Tc. The peak height of the hump decreases with the Mn content in both the Y- and Gd-based systems, barring GdBa2(Cu0.99Mn0.01)3O7−δ. The peak height reduction in the Gd-based cuprates is much faster (∼one fourth) compared to the Y-based samples. The thermoelectric powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…However we observe drastic reduction of T C for the sample with x = 0.02 which is either due to potential scattering [17] or due to reduction in the carrier (hole) density (caused by Mn +k , k > 2 ions) [15]. In our earlier communication we have shown that the features of the thermoelectric power and thermal conductivity rule out the latter possibility [14]. The observed temperature dependence of the specific heat (C P ), of GdBa 2 (Cu 1Àx Mn x ) 3 O 7Àd for different x is described elsewhere [14].…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…However we observe drastic reduction of T C for the sample with x = 0.02 which is either due to potential scattering [17] or due to reduction in the carrier (hole) density (caused by Mn +k , k > 2 ions) [15]. In our earlier communication we have shown that the features of the thermoelectric power and thermal conductivity rule out the latter possibility [14]. The observed temperature dependence of the specific heat (C P ), of GdBa 2 (Cu 1Àx Mn x ) 3 O 7Àd for different x is described elsewhere [14].…”
Section: Resultsmentioning
confidence: 62%
“…In our earlier communication we have shown that the features of the thermoelectric power and thermal conductivity rule out the latter possibility [14]. The observed temperature dependence of the specific heat (C P ), of GdBa 2 (Cu 1Àx Mn x ) 3 O 7Àd for different x is described elsewhere [14]. The pristine sample (x = 0.0) shows a jump in C P of amount DC P = 5.7 mJ/gK.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…They have shown that oxygen deficient samples show higher Z-values. However it is well-know that electrical conductivity, thermal conductivity and thermo-power strongly depend on nature of dopants and dopant concentration [8][9][10][11], thus, it would be interesting to explore other oxide superconductors where one can modify the stoichiometry and use suitable doping in order to achieve a fairly large value of Z.…”
Section: Introductionmentioning
confidence: 99%